LTE MIMO Closed Slot Antenna System for Laptops With a Metal Cover - Shu-Chuan Chen (IEEE Access, 2019)
This paper presents an LTE MIMO closed slot antenna system for laptops with a metal cover. Its main and auxiliary antennas have the same structure that measures 130 × 3 mm2. They are configured in a manner of reflection symmetry on the display metallic ground plane and are 5 mm away from the hinge. The distance between the two antennas is 20 mm, and the profile height of the MIMO antenna system is only 3 mm. This LTE closed slot antenna is excited by an exciter of 30 × 3 mm2 to cover the LTE eight-band operation (LTE700/GSM850/900/1800/1900/UMTS/LTE2300/2500). The exciter is a simple planar inverted-F antenna (PIFA) structure loaded with reactive matching elements, which can enhance the impedance matching in the desired frequency bands. This LTE MIMO closed slot antenna system has good isolation of at least 16 dB without adding any additional isolation elements. The measured antenna efficiency of the MIMO antenna system is larger than 40% in the low-frequency band and 50% in the high-frequency band, meeting the practical application requirements.